The practice of developing the academic cloud using the Proxmox VE platform - Vasyl Oleksiuk; Olesia Oleksiuk (Academy of Cognitive and Natural Sciences, 2021)
Cloud technologies provide users with efficient and secure tools for data management, computing, storage and other services. The article analyzes the projects for the introduction of cloud technologies in education and identifies the main advantages and risks in creating a cloud infrastructure for the university. Such startups contribute to the formation of a new paradigm of education. It involves the virtualization of education, the introduction of mobile and blended learning, ie the combination of cloud computing with modern learning concepts. In this paper, we highlight our experience in improving the academic cloud for the training of a bachelor's degree in computer science. This is through the integration of the Proxmox VE platform into existing computing power by deploying the Proxmox VE system. In the study, we reveal some technical and methodological aspects of the organization of the educational process using this corporate cloud platform. The scheme of the organization of physical components of cloud infrastructure (nodes, virtual networks, routers, domain controller, VPN server, backup system of students' virtual machines) is given. All characteristics of this environment and possibilities of their application are studied.